Management of Tooth Hypersensitivity Under a Cantilever Fixed Partial Denture Using a Novel Low-Level Laser Therapy Protocol: A Case Report - Fattouh, Mohamed; Aljuaid, Manal Mohammed; AbdelAleem, Nada Ali (UI Scholars Hub, 2023)
Tooth hypersensitivity is a common clinical complaint after dental treatment. Objective: This study presents a case report of the use of a diode laser for treating tooth hypersensitivity in a patient with a cantilever fixed partial denture abutment. Case Report: A 23-year-old female patient presented to the Faculty of Dentistry, Umm Al-Qura University in Makkah, with the chief complaint of pain in a deeply carious maxillary right first premolar. The tooth was extracted, and a cantilever fixed partial denture was placed using the second premolar as an abutment. One year later, the patient experienced tooth hypersensitivity under the bridge. Low-level laser therapy (LLLT) was implemented to treat cervical hypersensitivity using a novel protocol with a total application time of 2.5 minutes across two visits. LLLT effectively relieved the pain. Conclusion: Diode laser is a valid method for treating tooth hypersensitivity in fixed partial denture patients.